1976
DOI: 10.1021/i260060a016
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transfer to Pseudoplastic Fluids in an Agitated Vessel

Abstract: The vessel inside and coil outside film heat transfer coefficients of water and dilute aqueous polymer solutions of sodium carboxymethyl cellulose (SCMC) and sodium alginate (SA) have been studied in a turbine-agitated vessel for standard and nonstandard vessel configurations with agitator diameter, depth of agitation, helix diameter, and coiled tube outside diameter as parameters. The jacket-and coil-side heat transfer results are correlated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1978
1978
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Oldshue and Gretton (1957) were the fi rst to comprehensively study the effects of heat transfer with helical cooling coils. Suryanarayanan et al (1976) and Skelland and Dimmick (1969) studied heat transfer to shear-thinning fl uids in agitated vessels. Skelland and Dimmick (1969) present the most comprehensive work using power law fl uids and helical cooling coils in the transitional and turbulent fl ow regimes.…”
Section: Early Literaturementioning
confidence: 99%
“…Oldshue and Gretton (1957) were the fi rst to comprehensively study the effects of heat transfer with helical cooling coils. Suryanarayanan et al (1976) and Skelland and Dimmick (1969) studied heat transfer to shear-thinning fl uids in agitated vessels. Skelland and Dimmick (1969) present the most comprehensive work using power law fl uids and helical cooling coils in the transitional and turbulent fl ow regimes.…”
Section: Early Literaturementioning
confidence: 99%
“…Hence they are almost impossible to derive directly from theoretical mathematical equations. Many reports (Cummings and West, 1950;Oldshue and Gretton, 1954;Suryanarayana et al, 1976;Chilton et al, 1944) have used dimensional analysis to derive an equation of dimensionless groups to reduce the complicated interactions of the individual factors. Some heat transfer studies of conventional agitated vessels are listed in Table 1.…”
Section: Dimensional Analysismentioning
confidence: 99%
“…Pratt (1943) used a paddle and obtained the exponent of -0.25, and Jha and Rao (1967) used a turbine which gave on exponent of -0.27 for d < , as shown in Table 1. Suryanarayana et al (1976) considered that the smaller the value of d,, is, the strength of the fluid flowing over the helical-surface and the greater the heat transfer effect. These phenomena were also confirmed in this work.…”
Section: Efsect Of the Coil Pitchmentioning
confidence: 99%
“…Studies about the impeller geometry (i.e., diameter ratio D/T and tank height ratio C/T) have concluded that an increment in the diameter increases the heat transfer coefficient in radial impellers due to the higher turbulence caused by the increased Reynolds number …”
Section: Introductionmentioning
confidence: 99%
“…The use of the empirical correlations is restricted because they depend on the process from which they were obtained. Other studies in jacketed stirred tanks have focused on evaluating the influence of baffles [3,6] and the impeller type and size [4][5][6][7][8][9] on the heat transfer coefficient [6,8] using different working fluids.…”
Section: Introductionmentioning
confidence: 99%